Description of a new genus and species, Pseudobasidissus barclayi (Coleoptera: Anthribidae), from east Madagascar - Trýzna, Miloš; Baňař, Petr (Zootaxa, 2014)
A new genus and species, Pseudobasidissus barclayi Trýzna & Baňař gen. nov. et sp. nov. (Anthribidae: Anthribinae: Platyrhinini), from Madagascar is described. Male and female genitalia are studied and illustrated. Colour photographs of the holotype and genitalia of both sexes are provided. Comparison is made with the similar genus Basidissus Fairmaire.